Polyphenolic Compounds in Wine and Beer - Nardini, Mirella (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint describes the polyphenolic composition of wine and beer, with a special emphasis on extractive and analytical aspects. Furthermore, the effects of wine and beer polyphenols on human health are studied in the depth.